THE BILATERAL TRADE OF INDONESIA : THE GRAVITY MODEL APPROACH - Anggita, Riyandi Saras; Wahyudi, Setyo Tri (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to examine the trade of Indonesia with 10 top export partner from 2003-2013 using the gravity model of trade. The panel regression analysis with fixed  effect model was conducted in ordered to acknowledge the relationship among the independent variables (Constant Gross Domestic Product, Per Capita Gross Domestic Product, transportation cost, Real Effective Exchange Rate) on export of Indonesia with 10 partners. This study using secondary data with panel regression analysis and research instruments were tested using chow test, hausman test and classical assumption test. The panel regression result showed that simultaneously and partially Constant Gross Domestic Product, Per Capita Gross Domestic Product , transportation cost and Real Effective Exchange Rate had significant effect on export of Indonesia.Keywords  :  gravity model, export, constant gross domestic  product, per capita gross domestic product, transportation cost, real effective exchange rate